CHALLENGES OF E-PARLEMENT DEVELOPMENT: COMPARISON OF PRACTICE IN INDONESIA WITH OTHER DEVELOPING COUNTRIES - Randini, Hilda Piska; Prihandi, Natasya Arnanda; Dewi, Afiya Noor (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Electronic government (e-government) has become a paradigm-changing concept in public administration and the interaction of government with society. This transformation involves the implementation of information technology and the internet to improve efficiency, citizen-oriented services, transparency, participation, and trust in government. In parliament itself, the concept of e-parlement developed as an effort to increase transparency, efficiency, and public involvement in political processes and legislation. While this concept offers many benefits, some challenges need to be overcome. This research analyzes the implementation of e-parlement in developing countries, identifies challenges that need to be overcome, and provides lessons on the implementation of e-parlement in developed countries. The theoretical foundation covers aspects such as strategy, operations, technology, and digital transformation in the context of parliamentary digitalization. The source of data used in this study is secondary data from research related to the implementation of e-Parlement which has been researched and written in the form of articles that are then published in international journals indexed by Scopus. The method of searching for articles is carried out online, by searching through the Scopus and Google Scholar sites with the keyword